A Pan‐European Study of the C9orf72 Repeat Associated with FTLD: Geographic Prevalence, Genomic Instability, and Intermediate Repeats. Issue 2 (4th January 2013) - van der Zee, Julie; Gijselinck, Ilse; Dillen, Lubina; Van Langenhove, Tim; Theuns, Jessie; Engelborghs, Sebastiaan; Philtjens, Stéphanie; Vandenbulcke, Mathieu; Sleegers, Kristel; Sieben, Anne; Bäumer, Veerle; Maes, Githa; et al.
<x xml:space="preserve">Abstract</x> We assessed the geographical distribution of C9orf72 G4C2 expansions in a pan‐European FTLD cohort. The overall FTLD frequency was 9.98% with frequencies of 18.52% in familial 6.26% in sporadic patients. We demonstrated that C9orf72 transcriptional activity significantly decreased with increasing number of repeats of intermediate length (7 to 24 units), suggesting that they might act as predisposing alleles. Notably, we observed in expansion carriers increased frequencies of short indels in a GC‐rich, low complexity sequence adjacent to the G4C2 repeat. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>